A Free‐Standing and Ultralong‐Life Lithium‐Selenium Battery Cathode Enabled by 3D Mesoporous Carbon/Graphene Hierarchical Architecture. (20th November 2014) - Han, Kai; Liu, Zhao; Shen, Jingmei; Lin, Yuyuan; Dai, Fang; Ye, Hongqi
<x xml:space="preserve">Abstract</x> High capacity cathode materials for long‐life rechargeable lithium batteries are urgently needed. Selenium cathode has recently attracted great research attention due to its comparable volumetric capacity to but much better electrical conductivity than widely studied sulfur cathode. However, selenium cathode faces similar issues as sulfur (i.e., shuttling of polyselenides, volumetric expansion) and high performance lithium‐selenium batteries (Li–Se) have not yet been demonstrated at selenium loading >60% in the electrode. In this work, a 3D mesoporous carbon nanoparticles and graphene hierarchical architecture to storage selenium as binder‐free cathode material (Se/MCN‐RGO) for high energy and long life Li–Se batteries is presented. Such architecture not only provides the electrode with excellent electrical and ionic conductivity, but also efficiently suppresses polyselenides shuttling and accommodates volume change during charge/discharge. At selenium content of 62% in the entire cathode, the free‐standing Se/MCN‐RGO exhibits high discharge capacity of 655 mAh g−1 at 0.1 C (97% of theoretical capacity) and long cycling stability with a very small capacity decay of 0.008% per cycle over 1300 cycles at 1 C. The present report demonstrates significant progress in the development of high capacity cathode materials for long‐life Li batteries and flexible energy storage device.